Translation and the revitalization of the Yoruba language: cultural preservation and digital sustainability in Nigeria - Raphael Idowu Ibiowotisi (International Journal of Administration and Education (IJAE), 2026)
Indigenous language decline has become a major concern in multilingual societies where global languages dominate formal communication. In Nigeria, Yoruba, despite its rich literary tradition and large speaker population, faces pressure from globalization, urbanization, language shift, and the growing preference for English among younger generations. This study examines the role of translation in revitalizing the Yoruba language, focusing on cultural preservation and digital sustainability. Using a qualitative documentary research design anchored on Language Maintenance and Revitalization Theory, data were purposively drawn from translated literary texts, educational and religious publications, policy documents, digital language resources, online platforms, and scholarly works published between 2018 and 2025. The data were analysed thematically. Findings show that translation supports Yoruba revitalization by preserving oral traditions, proverbs, folktales, indigenous knowledge, and cultural expressions central to Yoruba identity. The study also reveals that artificial intelligence, machine translation, language corpora, online dictionaries, mobile learning applications, and social media expand opportunities for documenting, learning, and using Yoruba in digital spaces. Educational and religious translations further strengthen mother-tongue literacy, intergenerational transmission, and the language’s functional domains. However, weak language policy implementation, limited funding, inadequate technological infrastructure, shortage of trained translators, and English dominance continue to constrain revitalization efforts. The study concludes that translation is a strategic tool for cultural continuity, educational development, and digital inclusion.